Development of curved surface building modules assisted by Wingeom using the inquiry method in Grade IX at SMPN 1 Koto Baru, Dharmasraya Regency - Ridho Gambate; Nola Nari; Isra Nurmai Yenti; Elda Herlina; Ummu Huda (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mulawarman, 2026)
The primary issue in this study was the low learning outcomes of students at State Junior High School 1 Koto Baru, Dharmasraya Regency, as the packaged books on curved surface geometry lack guidance and activities that enable students to derive formulas for the material. The minimal use of technology, animation, and graphics in the material also made learning less enjoyable, which results in a lot of learning information not being absorbed by students during the learning process. To address this, there was a need for teaching materials that could improve students' learning outcomes. Therefore, the purpose of this research was to develop a module for curved surface geometry, based on inquiry assisted by Wingeom, to improve students' learning outcomes that was valid, practical, and effective. This type of research was Research and Development (R&D) using 4D model. This research produced a module containing a module cover, module foreword, table of contents, introduction, learning outcomes, learning objectives, concept map, instructions for use, learning activities, sample questions, practice questions, summary, competency test, glossary, answer key, and bibliography. The module products were validated by experts, and practicality and effectiveness tests were conducted by 21 students in grade IX of SMPN 1 Koto Baru in Dharmasraya Regency. The instruments used in this study included validation sheets, student response questionnaires analyzed using percentage formulas, and the students' learning outcome tests were analyzed using the N-Gain formula. The research findings indicate that the module on curved surface geometry, based on inquiry with the assistance of Wingeom, aims to improve student learning outcomes, as assessed by 3 validators with an average score of 79,44% in the valid category. The practicality was assessed by students at 82,83%, placing it in the very practical category. In terms of effectiveness, a score of 0,74 was achieved, categorized as high improvement.